2020
DOI: 10.3390/foods9101385
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Apple Pomace by Extrusion Processing: Studies on the Composition, Polymer Structures, and Functional Properties

Abstract: By-products of fruit and vegetable processing are an inexpensive and sustainable source of dietary fiber, potentially offering valuable functional properties such as water binding and thickening. Due to these favorable properties, they can be utilized to reformulate widely-consumed foods, e.g., bakery products or beverages. In this study, apple pomace was used as a model system to study whether extrusion technology affects food by-product functionality and thus has the potential to broaden the application of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(70 citation statements)
references
References 60 publications
12
58
0
Order By: Relevance
“…In our previous study [21], we showed that the complex viscosity of apple pomace can be increased by extrusion processing. Table 1 gives an overview of the process conditions and the resulting functional properties.…”
Section: Extrusion Conditions and Resulting Complex Viscositymentioning
confidence: 89%
See 4 more Smart Citations
“…In our previous study [21], we showed that the complex viscosity of apple pomace can be increased by extrusion processing. Table 1 gives an overview of the process conditions and the resulting functional properties.…”
Section: Extrusion Conditions and Resulting Complex Viscositymentioning
confidence: 89%
“…Table 1. The process parameters (specific mechanical energy (SME), material temperature (T M )) and complex viscosity of raw and extruded apple pomace from extrusion trails at a barrel temperature of 100 • C and a total feed rate of 10 kg•h −1 (published in [21]). To characterize the crucial components for the formation of high viscous dispersions, the impact of each fraction on the viscosity was investigated.…”
Section: Extrusion Conditions and Resulting Complex Viscositymentioning
confidence: 99%
See 3 more Smart Citations